Exploring Overreaction Hypothesis for Large Cap Stocks in the Indian Stock Market: An Empirical Evidence of Superior Returns in Nifty 50 - Parikh, Abhishek; Baruah, Mitali (Indian Journal of Finance, 2013)
The stock market usually overreacts to various global, economic, industry or company-specific news. This overreaction leads to the generation of excess returns through momentum for a short period, and contrarian for a longer period. In this regard, most of the previous studies focused on creation of excess returns through momentum and contrarian strategies. The present study aims to explore the overreaction hypothesis with a special focus on large-cap stocks of Nifty 50 stocks from the Indian equity market. The present study also tries to confirm whether the behavioral justification of overreaction occurs due to the traders' activity in the short run, and in the long run, whether the reversal of momentum (De Bondt&Thaler, 1985,1987; Jagadeesh&Titman, 1993,2001) is true or not for the large cap stocks. At the same time, it tries to identify if such profits were created, then was it only signaling any evidence of presence of risk-return trade off, or was it a real case of superior returns? The study tries to find out the reversal point as results of Nifty 50 stock returns were showing momentum followed by contrarian. For this purpose, monthly return data of Nifty 50 stocks for the period from January 2004 to December 2010 had been collected. Analysis was done with the help of ANOVA and inferences were drawn.